The current Conflict of the Faculties and the future of the study of religion/s - Fujiwara, Satoko (Religion, 2020)
The future of the study of religion/s cannot be aptly discussed without considering the future of all academic studies (the humanities, social and natural sciences). Based on my experience as a board member of the Science Council of Japan, I argue that there are two major urgent challenges that are shared by, but not unique to, academic studies conducted in Japan: namely, how and to what degree to meet demands for social relevance; and what to do with the Euro-Western model of modern sciences. I will focus on the former, which stems from the relationships between scholarship and state governance. Scholars of religion/s may miss opportunities to contribute to interdisciplinary debates if they continue identifying applied studies primarily with theology or interfaith enterprises, while being satisfied with neo-empiricism.